Legal Reasoning of Judge's Decision No. 70/PID.SUS-TPK/2024/PN JKT.PST. on Corruption in The Mining Sector from The Perspective of Prophetic Legal Justice - Rio Pradita Wibowo; M. Junaidi (Universitas Muhammadiyah Surakarta, 2025)
As a state of law, Indonesia must guarantee legal certainty to its people. This article aims to analyze the considerations of the judges of the Central Jakarta District Court case number 70/Pid.Sus-TPK/2024/PN Jkt. Pst. according to the view of prophetic legal justice, in addition to providing insight to judges so that they can create legal reasoning that supports legal certainty, both from the concept of legislation and the concept of legal justice. This research uses a juridical-normative approach method with data types in the form of primary and secondary data. The results of this study are first, the legal facts show that in this case the panel of judges who examined and tried case number 70/Pid.Sus-TPK/2024/PN Jkt. Pst. did not heed the philosophical, juridical and sociological aspects in accordance with the rules on Corruption Punishment in giving a verdict against the defendant. Second, Indonesia as a state of law adheres to divine justice. The judge's decision number 70/Pid.Sus-TPK/2024/PN Jkt. Pst. with the view of Prophetic Justice, the concept of prophetic justice encourages social, ecological, and spiritual responsibility in every legal policy, including in the natural resource sector.